Losing the Right to Challenge Arbitral Awards - GERGEOS, RANA GHASSAN (2025)
This dissertation addresses the loss of the right to challenge arbitral awards, particularly on Article 4 of the UNCITRAL Model Law on International Commercial Arbitration, which embodies the principal of waiver to object, stating that a party that proceeds with arbitration without timely objecting to a known procedural irregularity under a non-mandatory provision or a violation of the arbitration agreement is deemed to have waived its right to object. Although this regulation improves procedural efficiency and finality, its interpretation and application have been inconsistent between jurisdictions. This study conducts a doctrinal and comparative analysis of Article 4 , examining its legal foundation, practical function, and interaction with other key provisions of the Model Law, namely Articles 16 and 34, which address jurisdictional objections and applications to set aside arbitral awards. The dissertation evaluates how the waiver rule has been viewed and applied in jurisdictions that have adopted the Model Law by thoroughly reviewing travaux préparatoires, national legislation, and relevant case law. It also examines the limitations of waiver, which is its application to mandatory vs non-mandatory rules and the extent to which waiver can be achieved through agreement between the parties. The comparisons conducted by this study reveal both harmonised interpretations and discrepancies that challenge the claimed consistency of the Model Law. This dissertation concludes by identifying deficiencies in the current structure of Article 4 and suggesting amendments to enhance its clarity, consistency, and procedural fairness in international arbitration.